When Public Opinion Left Behind: The Case Rejection of Visa on Arrival for Russian Tourists - Hetri Pima Anggara (WIMAYA)
The Visa on Arrival is Indonesia's foreign policy instrument to boost tourism. Russia's invasion of Ukraine in February 2022 had an impact on the increasing arrival of Russian tourists to Indonesia. The increasing number of Russians was also directly proportional to the violative and negative sentiments about Russian tourists on social media, public demands to revoke their visa. Despite negative public opinion, the Indonesian government still maintained visa on arrival for Russians. This paper analysed the case study by using Doeser’s (2013) model on circumstances when democratic governments neglected public opinion in foreign policy, with its indicators: issue salience, elite debate, and elite perceptions of international gains. This qualitative research used social media analysis to deconstruct the public opinion on issue salience and causal process tracing was used to analyse the context and development of the case. Interviews were conducted to obtain information and confirm the findings. This study found that the neglected of public opinion was carried out because the case categorized as non-critical issue happened episodically thus had low salience. Low media coverage and asymmetrical elite debates resulted in elite consensus. Then, Indonesia avoided economic and political losses and maintained bilateral relations with Russia.